2018
DOI: 10.1139/cjb-2017-0178
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone profiling reveals fungal signatures and strong manipulation of infection cycle in theGymnosporangium juniper-virginianaedual-host plant system

Abstract: The aim of this work was to examine the function of phytohormones in the pathogenesis of cedar-apple rust, a fungal disease caused by Gymnosporangium juniper-virginianae Schwein. on Eastern red cedar (Juniperus virginiana L.) and crabapple trees (Malus spp. Mill.). Control cedar branchlets, gall tissues, fungal telial horns, as well as healthy and infected apple leaves were collected throughout fungal and plant development and used for profiling endogenous cytokinins (CK) and abscisic acid (ABA) by high perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
(4 reference statements)
2
7
0
Order By: Relevance
“…The dominance of c Z- and iP-type CKs in the hormone profiles of saprophytic and biotrophic fungal species suggests that the tRNA degradation is the predominant CK pathway in that kingdom ( Morrison et al, 2015b ; Moffatt et al, 2018 ). A fungal tRNA-isopentenyltransferase gene homolog ( MOD5 ) was first identified in yeast ( Saccharomyces cerevisiae ) ( Laten et al, 1978 ; Dihanich et al, 1987 ).…”
Section: The Steps Of 2mes-ck Production Via the Trna Degradation Patmentioning
confidence: 99%
“…The dominance of c Z- and iP-type CKs in the hormone profiles of saprophytic and biotrophic fungal species suggests that the tRNA degradation is the predominant CK pathway in that kingdom ( Morrison et al, 2015b ; Moffatt et al, 2018 ). A fungal tRNA-isopentenyltransferase gene homolog ( MOD5 ) was first identified in yeast ( Saccharomyces cerevisiae ) ( Laten et al, 1978 ; Dihanich et al, 1987 ).…”
Section: The Steps Of 2mes-ck Production Via the Trna Degradation Patmentioning
confidence: 99%
“…While it is unclear whether there is rust-derived cis-zeatin. A recent study confirmed that cis-zeatin was detected in G. juniper-virginianae induced gall tissues as well as the wet telia, but not in control cedar branchlets [ 33 ]. To verify the effect of G. yamadae derived CKs on the induction of galls, we firstly examined the CKs content in juniper and G. yamadae , and found that galls and the telia contained significantly higher concentrations of CKs than the control sample (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Subsequently, along with G. yamadae teliospores development and maturity, vesicular transport-related genes and additional starch and sucrose synthesis-related genes were up-regulated at the middle stage (II_GY_J) and numbers of energy metabolism-related genes were up-regulated in the late stage (III_GY_J), which suggested a general function of galls as a carbohydrate source for the growth of G. yamadae teliospores. Correspondingly, rapid changes in the water and nutrient content in the gall lead to an increase in osmotic pressure, which induces the expression of ABA synthesis-related genes and an increase in ABA content, especially during the formation of large numbers of teliospores (II_GY_J) [ 33 , 52 ]. Besides, genes involved in auxin signaling transduction pathway were also specifically up-regulated in II_GY_J, which possibly contributed to teliospores germination [ 20 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations